(3JMQjQ GdeLSWis - (3eMeO Hf eMeO Hf GdMSf, CHh LYaQ, fUjQ GdOjf GdWhSj , J (B672 (3g` s; (3HWdejhS GdMcjes ((3TjQGR s)
(3ChdgG (B:s
(3CMeO Gddg eHOC cd eHOC , hZGjI cd ZGjI hHYO , abO cfJ HQgI ef GdReGf , YGRekG Ydi Cf CMQQ dfaSi , hdSGFQ WdHI GdYde ef GdENhGf , cJGH GdeLSWi , GdefShH Edi HWdjehS GdbdhPi s
(3BNQgG (B:s
(3aEPG CJeefG LeY eG jZfi GdLGO SDGd ef hLhO eG jMJGL Edjg Edi hLhOg , hJUMjM eG jMJGL Edi JUMjMg adfNJe GdcJGH , hCbhd hEPG habfi Gddg JYGdi GGjVkG Ydi JeGe eG aUdJg hEfLGR eG hYOJg Je GdcJGH s
(3HgG WeS TOjO NGUI GdUaMGJ GdChdi efgG hjUYH bQGAI cKjQ ef GdehGVYs
(3jJab BNQgG eY BNQ GdfSNI GdChdi HGNJdGa ai HYV GdCdaGXs
(3cJHJ Hbde eged GdfbW CMjGfkG HgG LOGhd hCTcGds
(3fSNI NGeSI s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
Keywords: (3Gdadcs